(12(cos52+isin52))/(3(cos110+isin110))12(cos52+isin52)3(cos110+isin110)
= (12(cos52+isin52)(cos110-isin110))/(3(cos110+isin110)(cos110-isin110))12(cos52+isin52)(cos110−isin110)3(cos110+isin110)(cos110−isin110)
= (12(cos52cos110+isin52cos110-icos52sin110-i^2sin52sin110))/(3(cos^2 110-i^2sin^2 110))12(cos52cos110+isin52cos110−icos52sin110−i2sin52sin110)3(cos2110−i2sin2110)
= (12(cos52cos110+sin52sin110+i(sin52cos110-cos52sin110)))/(3(cos^2 110+sin^2 110))12(cos52cos110+sin52sin110+i(sin52cos110−cos52sin110))3(cos2110+sin2110)
= (12(cos(52-110)+isin(52-110)))/(3(cos^2 110+sin^2 110))12(cos(52−110)+isin(52−110))3(cos2110+sin2110)
= (12(cos(-58)+isin(-58)))/312(cos(−58)+isin(−58))3
= 4(cos58-isin58)